Business ethics and principles in the marketing industry: Systematic Literature Review - Nurul Hildha Afifa; Imam Mukhlis (CV. Lenggogeni Data Publishing, 2023)
The aim of the research is to know the literature of business ethics and principles in industrial marketing searches are conducted on publications from 2019 to 2023 for scientific literature, utilizing exclusively open access journals. When